2002
DOI: 10.1046/j.1365-3180.2002.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil metabolism of flupyrsulfuron in winter wheat crops

Abstract: The sulfonylurea herbicide flupyrsulfuron was applied post‐emergence in March at the rate of 10 g a.i. ha−1 on winter wheat crops. In the 0–8 cm surface soil layer of the crops grown on sandy loam and loam soils, the flupyrsulfuron half‐life was 64 and 40 days respectively. Flupyrsulfuron and its metabolites were not detected during both crops or 1 month after crop harvest in the 8–15 and 15–20 cm soil layers. Soil degradation of flupyrsulfuron successively generated the cyclization products 1‐(4,6‐dimethoxypy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
0
16
1
Order By: Relevance
“…When flupyrsulfuron was applied post‐emergence in March at the rate of 10 g ha −1 on winter wheat crops, we observed that its degradation in soil generated, successively, the pyrido[2,3‐ d ]pyrimidine cyclization product 1‐(4,6‐dimethoxypyrimidin‐2‐yl)‐7‐trifluoromethyl‐1,2,3,4‐tetrahydropyrido[2,3‐ d ]pyrimidine‐2,4‐dione ( 2) and the condensation product methyl 2‐(4,6‐dimethoxypyrimidin‐2‐ylamino)‐6‐trifluoromethylnicotinamide ( 3 ) corresponding to the elimination of the sulfonylurea bridge of flupyrsulfuron (Fig 1). 2, 3 The compounds 2 and 3 were the main metabolites of flupyrsulfuron in soil. The maximum concentration of the pyrido[2,3‐ d ]pyrimidine 2 in soil occurred 1.5 months after the application of flupyrsulfuron, and thereafter decreased; the maximum concentration of the 3 occurred 2.5 months after the treatment.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…When flupyrsulfuron was applied post‐emergence in March at the rate of 10 g ha −1 on winter wheat crops, we observed that its degradation in soil generated, successively, the pyrido[2,3‐ d ]pyrimidine cyclization product 1‐(4,6‐dimethoxypyrimidin‐2‐yl)‐7‐trifluoromethyl‐1,2,3,4‐tetrahydropyrido[2,3‐ d ]pyrimidine‐2,4‐dione ( 2) and the condensation product methyl 2‐(4,6‐dimethoxypyrimidin‐2‐ylamino)‐6‐trifluoromethylnicotinamide ( 3 ) corresponding to the elimination of the sulfonylurea bridge of flupyrsulfuron (Fig 1). 2, 3 The compounds 2 and 3 were the main metabolites of flupyrsulfuron in soil. The maximum concentration of the pyrido[2,3‐ d ]pyrimidine 2 in soil occurred 1.5 months after the application of flupyrsulfuron, and thereafter decreased; the maximum concentration of the 3 occurred 2.5 months after the treatment.…”
Section: Introductionmentioning
confidence: 97%
“…Bioassays with sugar beet as test plant indicated that the pyrido[2,3‐ d ]pyrimidine metabolite 2 has a herbicidal activity equivalent to that of flupyrsulfuron 3. Product 3 also has herbicidal activity, but somewhat lower than that of flupyrsulfuron and compound 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, chlorsulfuron has been used in wheat and barley, but could stay vigorous in the soil for more than a few years and harm legumes and oilseeds [9]. Flupyrsulfuron methyl-sodium which was reported as a new 5-substituted sulfonylurea herbicide used to control grasses and broadleaf weeds in cereals [10] it has less than one month residual life [11]. Since then, several other 5-substituted sulfonylureas which show similar characteristics have been reported [12][13][14].…”
Section: Introductionmentioning
confidence: 99%